Mevalonate Kinase Deficiency as A Cause of Periodic Fever- A Report of Two Cases - Hema Sameera Pinnam; Mahabaleshwar Mamadapur; Sabarinath Mahadevan; Varuni Pragya (Dr. Annil Mahajan, 2024)
Mevalonate kinase deficiency (MKD) is an exceedingly rare autosomal recessive inborn metabolism error characterized by mutations in the MVK gene, leading to impaired synthesis of cholesterol and isoprenoids. Two case reports of MKD in South India, shedding light on the disease's clinical heterogeneity are described here. The first case involves an eleven-month-old child with recurrent febrile attacks, joint pain, and a family history of similar complaints. In the second case, a 2-year-old born to consanguineous parents presents with severe manifestations, including joint deformities, developmental delay, and malnutrition. Exome sequencing confirmed the diagnosis, identifying specific mutations in the MVK gene.